Functional Glycopolypeptides: Synthesis and Biomedical Applications - Zhao Wang; Xiaojuan Zhang; Qing Lin; Jingjing Sun; Santanu Bhattachaya; Guosong Chen; Ruilong Sheng (Advances in Polymer Technology)
Employing natural-based renewable sugar and saccharide resources to construct functional biopolymer mimics is a promising research frontier for green chemistry and sustainable biotechnology. As the mimics/analogues of natural glycoproteins, synthetic glycopolypeptides attracted great attention in the field of biomaterials and nanobiotechnology. This review describes the synthetic strategies and methods of glycopolypeptides and their analogues, the functional self-assemblies of the synthesized glycopolypeptides, and their biological applications such as biomolecular recognition, drug/gene delivery, and cell adhesion and targeting, as well as cell culture and tissue engineering. Future outlook of the synthetic glycopolypeptides was also discussed.